ISSP 1995 - National identity I: Sweden - Svallfors, Stefan (Umeå University, 2009)
This survey is the Swedish part of the 1995 'International Social Survey Program' (ISSP), and it focuses on national identity. Respondents were asked to comment on various topics regarding national identity, such as how 'close' they felt to Sweden, national pride, Sweden's relations with other countries, and treatment of immigrants and minority groups. Those queried were asked to describe the pride they felt towards Sweden's accomplishments in the following areas: political influence, economics, social security, science and technology, sports, the arts, armed forces, history, and treatment of others. A series of questions probed for respondents' views regarding international relations, including foreign trade restrictions, international problem-solving attempts, foreign language education, the purchase of land by foreigners, the nationality of television programs and movies, and the benefits of membership in regional international organizations. Respondents were also asked to assess their countries´ treatment of minority groups and immigrants. Topics covered the preservation of minority traditions, the impact of immigrant groups on crime, the economy, the job market, cultural openness, special provisions for political refugees, and the citizenship process. Demographic variables include age, sex, education, marital status, personal and family income, employment status, household size and composition, occupation, religion, social class, union membership, political party, political orientation, race, ethnicity, language fluency, demographics of community, and citizenship.

Purpose:

ISSP aims to design and implement internationally comparable attitude surveys. The study in 1995 investigating National identity: Sweden.

Detta är den andra svenska studien inom det internationella forskningsprojektet ISSP. Temat för studien 1995 är ”National identity”. Detta är första gången studien genomförs på det här temat och har sedan genomförts ytterligare en gång på samma tema (SND 0805).

International Social Survey Program, ISSP, är ett globalt forskningsprojekt som har till uppgift att konstruera och genomföra internationellt jämförbara attitydstudier. Sedan 1985 har attityddata årligen samlats in och utgör nu en databas som är fritt tillgänglig för forskarsamhället. I dagsläget är 48 länder, från sex olika världsdelar, involverade i projektet. Genom bredden av medlemsländer skapas möjlighet till jämförelser i flera dimensioner. Det finns möjligheter att både jämföra länder som har en likartad samhällsstruktur och historia, och länder som skiljer sig påtagligt från varandra.

Sverige har varit medlem i ISSP sedan 1992 och det är Sociologiska intuitionen vid Umeå universitet som är huvudman för studierna i Sverige.

Sedan starten 1985 har attityder från flera olika områden undersökts. Vissa områden har återkommit genom åren, vilket gör det möjligt att även jämföra dem över tid.

Syfte:

ISSP har som syfte att konstruera och genomföra internationellt jämförbara attitydstudier. Studien för 1995 undersöker åsikter om nationell identitet.
ISSP 1995 - Åsikter om nationell identitet
Keywords: population migration; migration; regionalism; regionalism; culture; kultur; interpersonal relations; mellanmänsklig relation; discrimination; diskriminering; cultural identity; kulturell identitet; minority groups; minoritetsgrupp; CORS; CORS; Equality, inequality and social exclusion; Jämlikhet, ojämlikhet och socialt utanförskap; Minorities; Minoriteter; Cultural and national identity; Kulturell och nationell identitet; Social Sciences; Samhällsvetenskap; Sociology; Sociologi